2020
DOI: 10.15362/ijbs.v26i0.355
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in the Bahamian Workplace

Abstract: This paper reports the first known study on workplace bullying in The Bahamas. Over 2,000 people participated in an Internet-based study in the spring of 2020. The data suggest that 22% of the workforce may suffer from severe workplace bullying. This is a relatively high figure and is a potential cause for concern. While no difference in the rate of bullying between male and female workers was identified, the underlying associations which appear to put males and females at risk of workplace bullying vary. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…The modal household income bracket in 2019 was $30,000-$49,999. These results are in line with the general biases in favour of females participating in online surveys in The Bahamas (Fielding, 2020) and in favour of younger age groups (which occurs when using university-aged persons to start the snowball sample).…”
Section: Resultssupporting
confidence: 84%
“…The modal household income bracket in 2019 was $30,000-$49,999. These results are in line with the general biases in favour of females participating in online surveys in The Bahamas (Fielding, 2020) and in favour of younger age groups (which occurs when using university-aged persons to start the snowball sample).…”
Section: Resultssupporting
confidence: 84%
“…It is apparent that the results from this study support the conjecture that those who live their lives more closely aligned with the TCBs are more supportive of corporal punishment than others. As such, this study supports the findings of Fielding andBallance (2021a and2021b) which noted the role that pastors can play in forming attitudes (Fielding & Ballance, 2020); so any successful attempt to encourage residents of The Bahamas to change their outlook towards the use of corporal punishment can be expected to benefit from the support of pastors from a diverse group of Christian denominations.…”
Section: Discussionsupporting
confidence: 86%
“…Participants indicated that they did not support making corporal punishment illegal. This view seems in tension with the fact that exposure to corporal punishment as a child is linked to a life of victimisation, including workplace bullying (Fielding, 2020). The use of corporal punishment has also been linked to macrosocial effects beyond the individual, as corporal punishment has a negative association with innovation, and so, ultimately, on national development (Fielding & Ballance, 2019).…”
Section: Discussionmentioning
confidence: 99%